Potential Availability of Forage in Oil Palm Plantations in West Pasaman Regency. Issue 1 (1st April 2022) - Putri, A; Abdullah, L; Nahrowi
Abstract: Forage fodder can be obtained from various sources, one of which is from oil palm plantations. Oil palm plantations have enormous potential for the development of ruminant livestock. The purpose of this study was to determine the potential of forage biomass in oil palm plantations in the West Pasaman Regency. The research was carried out in different location with different plants aged 13 and 15 years with a land area of 2 ha each. Sampling was carried out randomly, each location is taken as many as 30 samples of forage samples using a 100 cm x 100 cm quadrant, for forage plant species identification, forage production, and storage carrying capacity. The results showed that 24 types of potential forage plant species were identified, including grasses, legumes, rumba (other indigenous plant species), and oil palm leaf midribs. Potential forage biomass was 994 thousand tons year -1, which is possible to supply forage with a carrying capacity of 436, 000 animal units year -1 . This number enables an additional population of cattle with 413, 352 AU in west pasaman regency in terms of forage biomass potency in soil palm plantation.